THE TECHNICAL INGENUITY OF AL-JAZARI AND ITS RELEVANCE TO CONTEMPORARY ENGINEERING AND DESIGN: KECERDIKAN TEKNIS AL-JAZARI DAN RELEVANSINYA DENGAN REKAYASA DAN DESAIN KONTEMPORER - Dirik, Mahmut (Indonesian Journal of Islamic History and Culture, 2023)
This paper explores the technical ingenuity of Al-Jazari, a 13th-century Muslim inventor, engineer, and polymath, and his relevance to contemporary technology and design. Al-Jazari's contribution to the history of technology is significant, as he is known for his pioneering inventions in various fields, including mechanics, automata, and fluid mechanics. His works are characterized by their intricate and sophisticated design, which not only served practical purposes but also revealed an artistic and aesthetic sensibility. Through an analysis of Al-Jazari's works, this article highlights the innovation and creativity that characterized his approach to technology and design. It shows how his inventions were based on a deep understanding of the fundamental principles of mechanics and fluid dynamics, as well as the use of novel materials and techniques. The influence of Al-Jazari's inventions on later developments in technology and design is also explored. It is shown how his ideas have influenced the design of modern machines and mechanisms. The article concludes with the assertion that Al-Jazari's technical ingenuity is of great importance to contemporary engineering and design. By studying Al-Jazari's works and ideas, engineers and designers can gain a deeper understanding of the fundamental principles of mechanics, fluid dynamics and materials science, as well as an appreciation for the artistry and aesthetic qualities of well-constructed machines. In addition, his inventions can serve as a source of inspiration for contemporary design, as they demonstrate the possibilities of combining functional efficiency with beauty and elegance. Overall, this article highlights the continued relevance of Al-Jazari's technical ingenuity to contemporary engineering and design.